Functional Features of Social Capital - Hakobyan, Karine (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
This article presents the analysis of functional features of social capital in modern society based on its systematized core elements (norms, values, rules, trust, friendship, reputation, culture, etc.). It treats social capital as a social relations system based on the moral values and norms adherence to which benefit to each member of a community and society as a whole. The paper shows the functional peculiarities of social capital at different institutional levels of the society and the mutual relations and connections of social capital with the institutional environment: social capital creates the latter, on the other hand, the state, in its turn, affects the socio-economic development of society and improvement of life quality. Social capital helps to increase the credibility of the institutions of the state and consolidation of nation. The indicator of social capital is reproduction and development of society, nations and mankind. Moreover, no community, unions and alliances can be considered as social capital, if they do not contribute to the achievement of this aim.
Keywords: .